Broad proteomic screen reveals shared serum proteomic signature in patients with psoriatic arthritis and psoriasis without arthritis. (13th August 2020) - Leijten, Emmerik; Tao, Weiyang; Pouw, Juliette; van Kempen, Tessa; Olde Nordkamp, Michel; Balak, Deepak; Tekstra, J; Muñoz-Elías, Ernesto; DePrimo, Samuel; Drylewicz, Julia; Pandit, Aridaman; Boes, Marianne; et al.
Abstract: Objective: To identify novel serum proteins involved in the pathogenesis of PsA as compared with healthy controls, psoriasis (Pso) and AS, and to explore which proteins best correlated to major clinical features of the disease. Methods: A high-throughput serum biomarker platform (Olink) was used to assess the level of 951 unique proteins in serum of patients with PsA ( n  = 20), Pso ( n  = 18) and AS ( n  = 19), as well as healthy controls (HC, n  = 20). Pso and PsA were matched for Psoriasis Area and Severity Index (PASI) and other clinical parameters. Results: We found 68 differentially expressed proteins (DEPs) in PsA as compared with HC. Of those DEPs, 48 proteins (71%) were also dysregulated in Pso and/or AS. Strikingly, there were no DEPs when comparing PsA with Pso directly. On the contrary, hierarchical cluster analysis and multidimensional scaling revealed that HC clustered distinctly from all patients, and that PsA and Pso grouped together. The number of swollen joints had the strongest positive correlation to ICAM-1 ( r  = 0.81, P  < 0.001) and CCL18 (0.76, P  < 0.001). PASI score was best correlated to PI3 ( r  = 0.54, P  < 0.001) and IL-17 receptor A ( r  = –0.51, P  < 0.01). There were more proteins correlated to PASI score when analysing Pso and PsA patients separately, as compared with analysing Pso and PsA patients pooled together. Conclusion: PsA and Pso patients share a serum proteomic signature, which supports the concept of a single psoriatic spectrum of disease. Future studies should target skin and synovial tissues to uncover differences in local factors driving arthritis development in Pso.